Climate change and media influence (Herald of Journalism, 2024)
The "climate change" refers to the long-term changes in the atmosphere, mostly caused by rising global temperatures. The primary drivers of these changes are human activities that emit greenhouse gases into the atmosphere. The objective of this research inquiry is to examine multiple facets, encompassing climate change ramifications on a global scale, portrayal in the media, level of public consciousness, governmental regulations and educational endeavors within Kazakhstan.This research employs a mixed-methods approach to investigate media coverage, public awareness, government actions and international cooperation pertaining to climate change. Examining media influence on public opinion in Kazakhstan, the study scrutinizes the role of journalists and media outlets in fostering awareness and action on climate change issues. The paper analyses information from authority organizations` surveys, opinion polls and Google Trends data.The media assumes a vital role in shaping public opinion and transmitting knowledge, with esteemed global publications like The Guardian and BBC. Although Kazakhstan is vulnerable to climate change, there have been significant advancements in media coverage. Nevertheless, there are ongoing obstacles such as the scarcity of resources and the lack of attention from media owners.The study has discovered a notable deficiency in the inclusion of climate change in national curriculum, impeding the acquisition of the necessary information to effectively handle climate-related issues. This research establishes a foundation for the ongoing cooperation of media outlets, governments, and international organizations in tackling the multifaceted issues brought by climate change, emphasizing the pursuit of sustainable development goals.
Keywords: climate change, media coverage, Kazakhstan, UN Sustainable Development Goals.